Reconstruction of Consumer Protection Regarding the Provision of Halal Features in the Marketplace from the Perspective of Maqashid Syariah - Pangaribuan, Rohid Ramadani; Permata, Cahaya (IHSA Institute, 2025)
Consumer protection in the marketplace is an important issue along with the increase in digital transactions in Indonesia. One aspect that needs to be considered is the provision of halal features on the marketplace to ensure that the products sold are in accordance with sharia principles. This study aims to analyze the regulation of halal features in the marketplace as well as the concept of consumer protection based on the perspective of Maqashid Sharia. The research method used is an empirical legal method with a statute approach and a conceptual approach. The results of the study show that although regulations regarding halal product assurance have been regulated in Law Number 33 of 2014 concerning Halal Product Assurance, there are still many marketplace platforms that have not provided halal features in a transparent manner, so that it has the potential to cause asymmetric information for Muslim consumers. From the perspective of Maqashid Sharia, the absence of halal features in the marketplace can hinder the fulfillment of the principles of hifz al-din (maintaining religion), hifz al-nafs (preserving the soul), and hifz al-mal (preserving property). Therefore, it is necessary to strengthen regulations and the responsibility of marketplaces in providing halal information symmetrically to improve the protection of Muslim consumers and realize fair transactions in accordance with sharia principles